Academic social environment and the self-concept in students in a national education institute from Lima north - Flores Morales, Jorge Alberto (2016)
The goal of the research was to determine the correlation between the quality of the school socialclimate and the self-concept. This research was basic, of descriptive level, correlational designand quantitative approach. The census population comprised a total of 164 students from apublic school, with ages between 16 and 18 years old. The technique used was the survey. Theinstrument to collect data was the questionnaire to evaluate the social climate in the institution(CECSE), created from the items of California School Climate and Safety Survey adapted byTrianes, et al (2006). Besides, the questionnaire of self-concept GARLEY de Belén García Torres.For the reliability of both instruments, it was needed Cronbach’s alpha, which results were: 0.73for the school social climate variable and 0.77 for the self-concept variable.In this research the conclusion was that there is a connection between the school social climate andthe self-concept, showing a positive correlational coefficient rs=0.495**, p value = 0.000<0.05in students of eleventh to twelfth secondary grade in the institution. Besides, there is no differencein the perception of self-concept of male and female students, since they both have a high level.Likewise, in the case of school climate, they consider the environment as positive.